Development of Android-Based Application on Biodiversity Material - Khairunnissa Arrumi (International Review of Social and Cultural Studies, 2025)
This study aims to develop an Android-based application on biodiversity to enhance public understanding of biodiversity and its relevance to daily life, while promoting active community involvement in conservation efforts. The research employed a research and development (R&D) methodology using the PLOMP model, which consists of five phases: preliminary investigation, design, realization/construction, test and evaluation, and implementation. The application, titled Biodiversity Games, integrates multimedia elements to support interactive and engaging learning experiences. Validation was conducted by peer reviewers, yielding an overall validity score of 93.4%. Specifically, the display aspect achieved a score of 87.5%, the learning objectives 96.87%, and ease of use 95.83%. These results indicate that the application is highly valid and feasible for use in educational settings. The implementation phase conducted at MTs Dar El Hikmah demonstrated that students found the application accessible, engaging, and helpful in understanding biodiversity topics. Feedback also suggested that the application enhances science literacy and student motivation. Minor revisions were recommended to improve visual clarity on smaller devices. Overall, the Biodiversity Games application has strong potential as an effective digital learning tool for biodiversity education in Indonesian schools.